Smart hydrogels with high tunability of stiffness as a biomimetic cell carrier. (25th January 2019) - Zhao, Han; Xu, Kang; Zhu, Peng; Wang, Chunli; Chi, Qingjia
Abstract: Human tissues are sophisticated ensembles of various distinct cell types encapsulated in the biomechanical cues of the extracellular matrix. It has been known matrix stiffness plays a pivot role in cellular events and tissue‐scale biological processes. Thus, materials that can mimic mechanical environments of tissues in vitro and possess wide, physiologically relevant elasticity are highly desirable. Hydrogels provide a good cell platform to mimic native cellular environment. However, the limited stiffness tunability, and hinders the efforts to reproduce the biomechanical microenvironment of many in vivo progresses. These problems have been addressed by the recently emerged great quantity of exquisitely designed smart hydrogels. Smart hydrogels that respond sensitively to external stimuli are good choices due to the convenience in regulating their mechanical properties. In this review, we summarize the latest progress in the development of stimuli‐responsive hydrogels as a cell carrier (platform for cell culture) which spans a wide range of stiffness. Different kinds of smart hydrogels corresponding to various stimuli, including pH, temperature, light, metal ions, and forces, are introduced and their stiffness modulation through physicochemical procedures are reported.